Multi Objective Lifecycle Budget Allocation for Fusion Power Plant Installation - Mubiru, Kizito Paul; Ssempijja, Maureen N (Optimality, 2024)
Successful installation of a fusion power plant demands a critical assessment of capital costs and operating costs. Reduction strategies for such costs are desirable in order to achieve an economically competitive position. The paper develops a multiobjective goal programming model and initially, the objective function is defined. The model seeks to minimize the deviation variables of the objective function, subject to the goal values of budgetary expenditure allocated to capital costs and operating costs of fusion power plant installation. The sum of deviations is minimized so that actual expenditure on capital costs (direct/indirect construction costs) and operating costs (fuel, waste management, maintenance, manpower) meets the projected expenditure. Using the simplex method, the standard minimization problem is solved. An illustrative example is presented that determines the optimal allocation of expenditure on capital costs and operating costs for fusion power plant installation. Results from the numerical example presented indicate that certain goals on capital costs (direct/indirect construction costs) and operating costs (fuel, waste management, maintenance, manpower) can be fully or partially achieved. This, however, depends upon the priority levels and targets set for budgeted expenditure; in line with the categories of fusion power plant installation costs. The solution approach enables satisfactory allocation of expenditure based on the priority levels or goals set for energy production. The multiobjective goal programming approach can be effective where relevant categories of costs can be prioritized if necessary. It ensures cost-effectiveness in installing fusion power plants.